2007
DOI: 10.1039/b706343a
|View full text |Cite
|
Sign up to set email alerts
|

When a G protein-coupled receptor does not couple to a G protein

Abstract: Classically, G protein-coupled receptors (GPCRs) relay signals by directly activating heterotrimeric guanine nucleotide-binding proteins (G proteins). Increasing evidence indicates that GPCRs may also signal through G protein-independent pathways. JAK/STATs, Src-family tyrosine kinases, GRKs/beta-arrestins, and PDZ domain-containing proteins have been suggested to directly relay signals from GPCRs independent of G proteins. In addition, our laboratory recently reported that the beta(2) adrenergic receptor (bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 54 publications
0
46
0
Order By: Relevance
“…Surprisingly, it has been recently proposed that some GPCRs do not couple to G proteins and then are able to activate ERK1/2 by a G protein-independent signaling. In M a n u s c r i p t 10 fact, Jak/STATs, Src-family tyrosine kinases, GRKs/β-arrestins, and PDZ domaincontaining proteins have been suggested to relay signals from GPCRs, independent of G proteins, which could result in ERK1/2 activation (Sun et al, 2007). The single report on MC5R signaling states that this receptor activates the Jak/STAT pathway on Blymphocytes (Buggy, 1998) but the involvement of the ERK1/2 signaling cascade is not referred.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, it has been recently proposed that some GPCRs do not couple to G proteins and then are able to activate ERK1/2 by a G protein-independent signaling. In M a n u s c r i p t 10 fact, Jak/STATs, Src-family tyrosine kinases, GRKs/β-arrestins, and PDZ domaincontaining proteins have been suggested to relay signals from GPCRs, independent of G proteins, which could result in ERK1/2 activation (Sun et al, 2007). The single report on MC5R signaling states that this receptor activates the Jak/STAT pathway on Blymphocytes (Buggy, 1998) but the involvement of the ERK1/2 signaling cascade is not referred.…”
Section: Discussionmentioning
confidence: 99%
“…The implication is that b-arrestin is able to recruit Src kinase as part of a larger scaffold which, following ligand binding, allows the activation of the kinase by b-arrestin. Furthermore, it has also been suggested that the b2AR can interact directly with Src kinase to facilitate delayed activation of the MAPK pathway (Huang et al, 2004;Sun et al, 2007).…”
Section: Journal Of Cell Sciencementioning
confidence: 99%
“…In addition, just as there is heterogeneity in the G protein array available for 7TMR interaction, there are data to suggest that ␤-arrestin is functionally diverse as well (Shukla et al, 2008). Finally, it should be noted that 7TMR signaling and behavior can also be mediated by other cytosolic proteins in addition to G proteins and ␤-arrestin (Bockaert and Pin, 1999;Heuss and Gerber, 2000;Brady and Limbird, 2002;Bockaert et al, 2004;Lanier, 2004;Gavarini et al, 2006;Sun et al, 2007b). Current data for agonist bias most often report effects seen with synthetic agonists, but there is at least one 7TMR in which it is operative for natural ligands.…”
Section: Operational Mechanisms Of Functional Selectivity a Historimentioning
confidence: 99%